The Implementation of the Problem-Based Learning Model in Developing Civic Disposition among Elementary School Students - Rahayuningsih, Apriliana Sri; Suryandari, Kartika Chrysti; Rawanoko, Endrise Septina (Universitas Sebelas Maret, 2026)
Civic education in elementary schools plays a crucial role in developing students’ civic disposition; however, current learning practices still predominantly emphasize cognitive aspects rather than affective and behavioral dimensions (Torney-Purta et al., 2015; Zubaedi, 2015). This study aims to systematically review research on the implementation of Problem-Based Learning (PBL) in developing civic disposition among elementary school students. The method used is a Systematic Literature Review (SLR) following the PRISMA framework, including identification, screening, eligibility, and inclusion stages. A total of 15 articles published between 2015 and 2025 were analyzed from SINTA-indexed journals, reputable international journals, and Scopus-indexed sources. The findings reveal that PBL enhances student engagement, critical thinking, collaboration, and social responsibility (Hmelo-Silver, 2015; Barrows, 2012; Anazifa & Djukri, 2017). Although most studies focus on cognitive outcomes, PBL also contributes to civic disposition development, including social awareness, participation, and responsibility. However, studies explicitly examining civic disposition remain limited. Therefore, further research is needed to strengthen empirical evidence.